Analysis of Student Difficulties in Understanding The Concept of Newton's Law of Motion - Muhammad Erfan; Tursina Ratu (STKIP Singkawang, 2018)
The aim of this study is to investigate the difficulties experienced by students on the concept of Newton’s Law of Motion. The method used is descriptive analysis with a sample of 14 students who take Mechanics Course on Physics Education Study Porgram, Faculty of Teacher Training and Education of Samawa University. The data was collected by essai test. Based on the test result show that (1) students have difficulty in integrating mathematical equation. (2) students was unable to operated integration and differentiation related to trigonometric function. (3) students have not understood the concept of potential in conservative force field.